Religious Stories in Transformation: Conflict, Revision and Reception - Houtman, Alberdina; Ḳadari, Tamar; Poorthuis, Marcel; Ṭohar, Ṿered (Jewish and Christian perspectives series, 2016)
Preliminary Material -- 1 Introduction /Alberdina Houtman , Tamar Kadari , Marcel Poorthuis and Vered Tohar -- 2 Storytelling and Meaning: Theory and Practice of Narrative Variants in Religious Texts /Eli Yassif -- 3 The Adamic Myth from Canaan /Marjo Korpel -- 4 The Development of the Adamic Myth in Genesis Rabbah /Alberdina Houtman -- 5 First Man, First Twins: The Origins of Humankind in Zoroastrian Thought /Albert de Jong -- 6 The Fall of Iblīs and its Enochic Background /Tommaso Tesei -- 7 Interreligious Aspects in the Narrative of the Burial of Adam in Pirkei de-Rabbi Eliezer /Adiel Kadari -- 8 Aggadic Motifs in the Story of Jonah: A Study of Interaction between Religions /Tamar Kadari -- 9 Jewish Legal Practice and Piety in the Acts of the Apostles: Apologetics or Identity Marker? /Eyal Regev -- 10 Bound in Righteousness: Variances and Versions of the Aqedah Story in Jewish Hymnography (Piyyut) /Wout van Bekkum -- 11 The Biblical Stories about the Prophet Elijah in Early Syriac-Speaking Christianity /Gerard Rouwhorst -- 12 Sūrat Yūsuf (xii) and Some of Its Possible Jewish Sources /Meir Bar-Ilan -- 13 The Well of Miriam and Its Mythological Forebears /Jan Willem van den Bosch -- 14 Bethlehem and the Birth of the Messiah in the Eyes of a Byzantine Jewish Storyteller: Rebuke or Consolation /Paul Mandel -- 15 The Infallibility of the Prophets and the Fallible Jesus in Islam: On the Transformation of a Jewish Story into an Islamic Anti-Christian Polemic /Marcel Poorthuis -- 16 On Marrying and Divorcing a Demon: Marriage and Divorce Themes in the Jewish, Christian, and Pagan World /Margaretha Folmer -- 17 Ascension Traditions in Jerusalem /Michael Ehrlich -- 18 Waiting for the Harvest: Trajectories of Rabbinic and “Christian” Parables /Eric Ottenheijm -- 19 Reading Chad Gadya through the Kaleidoscope of Time /Meir Seidler -- 20 Ẓemaḥ Ẓaddik by Leon of Modena: Between Two Worlds /Vered Tohar -- 21 “We do not pray, we invent”: Jews, Judaism, and Jewish Mysticism in the Video Game “Wolfenstein: The New Order” /Frank G. Bosman and Leon Mock -- 22 Power Women: The Retelling of Sacred Narratives in an Interreligious Context /G.M. Speelman -- 23 Biblical Murals in Medieval Frisian Churches /Gert van Klinken -- 24 Sinai—The Mountain of God /Shulamit Laderman -- Index of Names -- Index of Sources.